Analisis Leverage, Profitabilitas dan Economic Value Added Terhadap Kualitas Laba pada Perusahaan Sektor Industri Dasar dan Kimia - Ledy Mutiara Salsalina Br Tarigan; I. Ganda Pardosi; Susanti Melan Sijabat; Jholant Bringg Luck Amelia Br Sinaga; Munawarah Munawarah (IPM2KPE, 2023)
This research aims to analyze, determine the impact, gather knowledge and understand the impact of leverage, profitability and economic value added on the quality of profits of companies in the basic and chemical industries listed on the IDX. The method used in this research is a quantitative method that explains the relationship between variables and the theory test used. The research results show that financial leverage and profitability have no and negligible influence on earnings quality, while economic added value has a large and significant influence on earnings quality in chemical and basic industrial companies listed on the IDX. From the R-Square value, it can be seen that 99.8% of the dependent variable can be explained by the independent variable. Keywords: Economic Value Added, Quality of Earnings, Leverage, Profitability